Geophysical assessment and geotechnical investigation of quick‐clay landslides – a Swedish case study. Issue 3 (1st January 2013) - Malehmir, Alireza; Bastani, Mehrdad; Krawczyk, Charlotte M.; Gurk, Marcus; Ismail, Nazli; Polom, Ulrich; Perss, Lena
Abstract : We present a preliminary assessment of the potential utility of various geophysical measurements carried out over a quick‐clay landslide site in south‐west Sweden. The multidisciplinary approach includes active P‐ and S‐wave seismic investigations, including 2D and 3D reflection and refraction surveys, passive single and 3C seismic surveys, electrical resistivity tomography and electromagnetic surveys including controlled‐source and radio‐magnetotellurics, ground‐penetrating radar and potential field studies. The P‐wave and particularly S‐wave reflection seismic data show a high‐resolution image of bedrock topography and the stratigraphy of a 100 m thick sequence of sediments that lies on top, which include lightly consolidated quick‐clays. Of particular interest is the identification of a layer of relatively coarse‐grained material between 10–20 m below the ground surface. Geotechnical investigations indicate that most but not all quick‐clays at the site are located above this layer. Further studies are required to determine the importance of their relationship and whether the coarse‐grained layer may have had a role in triggering quick‐clay landslides in the region. Geoelectrical and electromagnetic methods provide high‐resolution images of the unconsolidated subsurface and particularly the normal and leached clays. Radio‐magnetotelluric methods proved valuable near the river where traditional geoelectrical methods failed to provide sufficient depth coverage. The study shows that geophysical data are able to image major subsurface structures associated with quick‐clay landslides.